Is the rand a commodity currency? A volatility spillover analysis. Issue 3 (3rd July 2022) - Sayed, Ayesha; Charteris, Ailie
ABSTRACT: South Africa is a major commodity exporter, yet it is not clear what impact volatility in commodity prices has on the volatility of its currency. In this study, we examine whether a comprehensive sample of commodities (metals, grains and energy) transmit (or receive) volatility spillovers to (from) the rand exchange rate against the United States dollar for the period January 2000 to May 2022. This study uses the dynamic connectedness and volatility spillover approach of Diebold and Yilmaz (2012, 2014) and Gabauer (2020). Our findings highlight the rand as a net receiver of volatility from almost every commodity examined, with silver and palladium exhibiting the strongest volatility spillover onto the rand. From a transmission perspective, there is some evidence that the rand can be considered a commodity currency for metal exports but there may also be other channels to explain the impact of these commodities on the currency. The results have important implications for policymakers, currency traders and hedgers in commodity markets.